Towards a just sustainability transition in tourism: A multispecies justice perspective. (September 2022) - Rastegar, Raymond
Abstract: Despite increasing attention to questions of justice, particularly in academia, this has not necessarily impacted on tourism policy and practice. Evidence shows how unjust structures of the contemporary tourism system built on dominant humanism frameworks have been unable to address justice issues such as the omission of non-western perspectives or exclusion of marginalised groups and nonhuman actors. The dominance of traditional economic thinking such as neo-liberal growth policies has resulted in increasing claims of injustice that serves to threaten the long-term sustainability and growth of the tourism sector. Confronting such complexities, this paper uses a multispecies justice lens to explore the main narratives of justice and justice domains by considering a larger mixed moral community in the tourism landscape. Identifying a social-natural sciences divide, this work calls for a just sustainability transition in tourism research, policy, and practice. The concept of just sustainability transition proposed in this work is a longitudinal process with transitional steps demonstrating measurable outcomes from actions to move towards not only more sustainable, but also more just tourism futures for humans and nonhumans.